As manifestações da flexibilidade na arquitetura - Pedrotti, Nayara Pires (2019)
Flexible architecture is the subject of long discussions in contemporary times. The technological development and the arrival of innovations in the universe of flexible architecture collaborated so that the habitual meaning of the concept of flexibility lost force, being confused with other synonyms of the word, being the architecture adaptable, versatile, modular, movable, elastic, remontável, ephemera , etc. When the theme is brought up, it is generally understood as an architecture that can meet users' needs through plant flexibility through moving partitions, but seeing flexibility only in this way may limit the real meaning of the concept studied here. The objective of this research is to understand how flexibility can manifest in projects of the most varied types, in addition to what their effects are for contemporary society. In order to do so, it was decided to study the question after the second half of the twentieth century, since it is a period in which post-war reconstruction and industrial development have boosted the sophistication of the programs. In order for the objectives to be achieved, this research will have a bibliographical survey throughout the study period; specific research of the concept flexibility according to the view of several authors; mapping and data collection of projects to analyze the flexibility, compare the different ways of understanding it inserted in the architectural project and finally analysis of the results obtained.